Performance of RCC used for overtopping protection and spillways - Hansen, Kenneth D., author; Fitzgerald, Thomas J., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
Roller-compacted concrete (RCC) has become the most widely accepted method for providing safe overtopping protection for embankment dams in the United States. The concept consists of placing horizontal layers of erosion resistant RCC on the downstream slope of existing dams to increase spillway capacity during extreme rainfall events. Since the first earth dam with an RCC overlay was constructed in 1984, more than 130 such projects have been put in service. Because most of these hydraulic upgrades were designed to accommodate rare flow events, there was little information initially available of their actual performance when overtopped. With more RCC overtopping protection in service, there are now more examples of floods in excess of the 1 in 100 year event overtopping RCC protected dams. This paper will present data on the performance of RCC overlay projects when overtopped and lessons learned from these actual examples.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: roller-compacted concrete (RCC); overtopping; protection; spillways